2020
DOI: 10.3389/fcell.2020.555378
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell-Produced Components of Extracellular Matrix Potentiate Multipotent Stem Cell Response to Differentiation Stimuli

Abstract: Extracellular matrix (ECM) provides both structural support and dynamic microenvironment for cells regulating their behavior and fate. As a critical component of stem cell niche ECM maintains stem cells and activates their proliferation and differentiation under specific stimuli. Mesenchymal stem/stromal cells (MSCs) regulate tissue-specific stem cell functions locating in their immediate microenvironment and producing various bioactive factors, including ECM components. We evaluated the ability of MSC-produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 104 publications
2
42
0
Order By: Relevance
“…ECM proteins, such as laminin, fibronectin and N-cadherin were found to be increased greatly in hPDSLCs cultured on TEST. Fibronectin belongs to one of the principal adhesion protein family for eukaryotic cells, which plays a key role in binding to integrins as well as other extracellular components including collagen, fibrin and proteoglycans [ 50 ]. N-cadherin is a key factor in directing cell–cell interaction during the mesenchymal condensation and it is also considered as a mimetic peptide that enhanced the osteogenic differentiation of the MSCs, leading to bone matrix deposition on the titanium implants [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…ECM proteins, such as laminin, fibronectin and N-cadherin were found to be increased greatly in hPDSLCs cultured on TEST. Fibronectin belongs to one of the principal adhesion protein family for eukaryotic cells, which plays a key role in binding to integrins as well as other extracellular components including collagen, fibrin and proteoglycans [ 50 ]. N-cadherin is a key factor in directing cell–cell interaction during the mesenchymal condensation and it is also considered as a mimetic peptide that enhanced the osteogenic differentiation of the MSCs, leading to bone matrix deposition on the titanium implants [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…This microenvironment is composed by an ECM of collagens, adhesion proteins, proteoglycans, and growth factors, forming the stem cell niche ( Fuchs et al, 2004 ; Moore and Lemischka, 2006 ). ECM and cells establish a synergistic relationship: ECM provides appropriate cues to cells while cells secrete molecules that influence the ECM composition ( Novoseletskaya et al, 2020 ). Additionally, stem cell behavior is dependent on biophysical aspects of the microenvironment, such as tissue stiffness, which is regulated by ECM organization and composition ( Engler et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these cells might be preferred for studies investigating the therapeutic potential of MSC secretome. Thus, we recently reported that the extracellular matrix, produced by hTERT-immortalized MSCs, could potentiate the sensitivity of the primary stem cells to differentiation stimuli and hold a promising option to functionalize biomaterials for tissue engineering ( Novoseletskaya et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%